Pictorial essay: USG of lumps and bumps of the foot and ankle - Botchu, Rajesh; Khan, Aman; Bhatt, Raj (Indian Journal of Radiology and Imaging, 2010)
USG is a cost-effective and dynamic way to interrogate superficial lumps and bumps. We present a pictorial review of the USG findings in various "lumps and bumps" of the foot and ankle.
Keywords: Foot; lumps; sonography